Kajian Pembelajaran Baca Tulis Al-Qur’an - Muhammad Aman Ma’mun (Jurnal Pendidikan Islam, 2019)
Abstract: Preferably the human is the one who learns the Qur'an and teach it. So learning to read the Qur'an to be conducted early as the provision of life and afterlife. Learning the Quran as an interaction learning activities also have a purpose. The purpose of learning the Qur'an is as follows: 1) so that students can read Quran fluently and correctly according to the recitation. 2) so students can familiarize the Qur'an in his life. 3) enrich the vocabulary words and sentences that are beautiful and interesting. In Indonesia there are various methods of reading the Qur'an as may have been collected by the LITBANG in 1994. A variety of methods have advantages and disadvantages of each. One method is to write the Qur'an by dictation. There are four (4) types of dictation that can be applied to a person according to their cognitive level: Imla’ manqu, Imla’mandhur, Imla’ ghairu al-mandhur (masmu’), Imla’ ikhtibari.